2004
DOI: 10.1002/hed.20074
|View full text |Cite
|
Sign up to set email alerts
|

CO2 laser surgery: A larynx preservation alternative for selected hypopharyngeal carcinomas

Abstract: TLS is an alternative for the treatment of selected HC associated with a high larynx preservation rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
40
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 35 publications
(38 reference statements)
11
40
0
3
Order By: Relevance
“…Airway fire is perhaps the most feared complication and strict caution against it cannot be overemphasized. Other potential complications include bleeding, granulation tissue formation, and aspiration pneumonia [2,16,22]. A low incidence of major complications was found for TLM cases in this series (Table IV).…”
Section: Journal Of Surgical Oncologymentioning
confidence: 68%
See 3 more Smart Citations
“…Airway fire is perhaps the most feared complication and strict caution against it cannot be overemphasized. Other potential complications include bleeding, granulation tissue formation, and aspiration pneumonia [2,16,22]. A low incidence of major complications was found for TLM cases in this series (Table IV).…”
Section: Journal Of Surgical Oncologymentioning
confidence: 68%
“…It has been previously shown that selected hypopharyngeal cancers of all classifications can be successfully treated with TLM [2,16]. This has been especially evident in cases with early disease.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Vilaseca et al [231] report on a cohort of 28 patients treated with transoral laser microsurgery, neck dissection and postoperative radiotherapy. Two patients had primary tumors classified as pT1, 16 as pT2, 9 as pT3, and 1 as pT4.…”
Section: Carcinomas Of the Hypopharynxmentioning
confidence: 99%